A2_1 Deep Space 1: Staying Cool - Forster, James; Bryan, Mark; Stone, Alex (Physics Special Topics, 2012)
In order to undertake an interstellar mission, as with normal space missions, cooling is of great importance as there are no ways for convection or conduction to remove excess heat. This paper will study the ability of radiative cooling to remove heat from a system and show that it is unsuitable for dealing with the energy requirements of such a vessel and indeed cooling systems cannot even handle the transportation of said heat.